166k views
2 votes
A) (x-1)^3+ 3x(x-4)+2=x^3
B) x^3 +6x +12x +8=0

User ByJeevan
by
6.1k points

1 Answer

1 vote

Answer: I'll solve A) since there is a lot of work to be shown.

Explanation:

A)

(x−1)³+3x(x−4)+2=x³

Use binomial theorem to expand (x−1)³

x³- 3x² + 3x - 1 + 3x(x-4) + 2=x³

Use distributive property on 3x(x-4)

x³- 3x² + 3x - 1 + 3x²-12x + 2=x³

Add like terms

x³ −9x + 1 =x³

Subtract x³ from both sides.

x³ −9x +1 -x³ = 0

Add x³ and -x³

−9x+1=0

Subtract 1 from both sides. Anything subtracted from zero gives its negation.

−9x=−1

Divide both sides by -9.

x= 1/9

User AgiaLab
by
5.4k points